Bending behavior of high‐performance, micro‐reinforced concrete. (8th November 2018) - Busse, Daniel; Empelmann, Martin
Abstract : The development of high‐performance concretes enables a reduction of the dimensions of concrete members. If these dimensions are reduced down to the size of 30–50 mm, a conventional reinforcement cannot be used and alternative concepts are required. In this case, micro‐reinforced concrete, internationally also known as ferro‐cement, can be used advantageously. In this paper, results of bending tests on micro‐reinforced beams made of high and ultra‐high performance concrete with varying micro‐reinforcement ratios and orientations are presented. Furthermore, approaches based on DIN EN 1992‐1‐1 (EC 2), allowing the determination of a minimum micro‐reinforcement ratio as well as the secure assessment of the ultimate flexural strength of micro‐reinforced beams were developed based on the test results. In addition, a finite element analysis of the beams is shown, enabling a precise recalculation of the load‐bearing behavior as well as the ultimate flexural strengths obtained during the tests. Overall, the described experimental and theoretical investigations are a valuable contribution towards the development of a general design approach for thin‐walled, micro‐reinforced concrete members.